Onychoheterotopia in children - Marco Ferrari; Vittorio Mazzarello; Egidio Barbi (PAGEPress Publications, 2021)
The ectopic nail (EN) is an additional nail located in an abnormal site. It belongs to the onycho-heterotopia, a rare condition whose pathogenesis is indeterminate. This article illustrates the clinical-morphological and dermoscopic points of view, the diagnostic criteria, the possible pathogenesis, and surgical treatment of this pediatric onychoheterotopia.